2000
DOI: 10.1007/s004240000379
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial chloride conductance in amphibian skin: regulatory mechanisms and localization

Abstract: The transepithelial transport of Na+ by amphibian skin must be accompanied by the corresponding anion, Cl-, and much effort has been devoted to the characterization of Cl- transport. The transepithelial Cl- conductance, G(Cl), is activated by voltage and adenosine 3',5'-cyclic monophosphate (cAMP), shows rectification, requires the presence of Cl- in the pathway and is influenced by factors modifying intracellular signalling cascades and by metabolic poisons such as cyanide (CN-). Until recently, these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…It was not possible to determine the transepithelial anion conductance in the low resistance larval integument (Table 1), whereas no finite Clconductance could be found in the high resistance skin of the adults following metamorphosis. It will be interesting to find out whether the voltage-activated conductance that characterizes toad skin (Larsen, 1991;Nagel et al, 2000) can be found in the skin of adult urodeles. Whatever may be the function of band 3 protein in MR-like cells, our experiments do not permit to make any conclusion on the possible association of MR cells and band 3 across the integument of S. salamandra to anion conductance (Larsen, 1991;Devuyst et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to determine the transepithelial anion conductance in the low resistance larval integument (Table 1), whereas no finite Clconductance could be found in the high resistance skin of the adults following metamorphosis. It will be interesting to find out whether the voltage-activated conductance that characterizes toad skin (Larsen, 1991;Nagel et al, 2000) can be found in the skin of adult urodeles. Whatever may be the function of band 3 protein in MR-like cells, our experiments do not permit to make any conclusion on the possible association of MR cells and band 3 across the integument of S. salamandra to anion conductance (Larsen, 1991;Devuyst et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Skin epithelium of adult amphibians is specialized in ions and water transport (Larsen, '91;Nagel et al, 2000 for reviews), particularly active Na þ transport. The latter is carried out through the principal cells compartment, and it has been analyzed down to the molecular level (reviewed in Garty and Palmer,'97).…”
Section: Ontogenetic Changes In Amphibian Skin Transportmentioning
confidence: 99%
“…The absorptive system is located in the epithelium, the secretory system resides in the exocrine skin glands. Active transepithelial Na + absorption proceeds across the principal cells whereas Cl -follows passively via either the mitochondria-rich cells or the paracellular pathway [16,18]. The active uptake of Na + via the principal cells can be described by the two-membrane model [14].…”
Section: Introductionmentioning
confidence: 99%